Learning curve of percutaneous endoscopic transforaminal lumbar discectomy by a single surgeon. Issue 4 (29th January 2021) - Son, Seong; Ahn, Yong; Lee, Sang Gu; Kim, Woo Kyung; Yoo, Byung Rhae; Jung, Jong Myung; Cho, Joon
Abstract : Abstract: To evaluate the learning curve of percutaneous endoscopic transforaminal lumbar discectomy (PETLD) from the novice stage to the proficient stage, we performed retrospective study for patients with lumbar disc herniation who underwent PETLD performed by a single surgeon and evaluated the surgeon's learning curve and the effect of surgical proficiency on outcomes. A total of 48 patients who underwent PETLD at the lower lumbar level (L3–S1) with a minimum 1-year follow-up were enrolled. The learning curve of the surgeon was assessed using cumulative study of operation time and linear regression analyses to reveal the correlation between operation time and case series number. Because the cutoff of familiarity was 25 cases according to the cumulative study of operation time, the patients were allocated into two groups: early group (n = 25) and late group (n = 23). The clinical, surgical, and radiological outcomes were retrospectively evaluated and compared between the two groups. According to linear regression analyses, the operation time was obtained using the following formula: operation time (minutes) = 69.925–(0.503 × [case number]) ( P  < .001). As expected, the operation time was significantly different between the two groups (mean 66.00 ± 11.37 min in the early group vs 50.43 ± 7.52 min in the late group, P  < .001). No differences were found between the two groups in demographic data and baseline characteristics. Almost all clinical outcomes (including pain improvement and patient satisfaction), surgical outcomes (including failure, recurrence, and additional procedure rates), and radiological outcomes (including change of disc height and sagittal angles) did not differ between the two groups. However, the late group demonstrated a more favorable postoperative volume index of the remnant disc (362.91 mm 3 [95% confidence interval, 272.81–453.02] in the early group vs 161.14 mm 3 [95% confidence interval, 124.31–197.97] in the late group, P  < .001), and a lower complication rate related to exiting nerve root (16.0% in the early group vs 0% in the late group, P  = .045). The learning curve of PETLD is not as difficult as that of other minimally invasive spine surgery technique. Although the overall outcomes were not different between the groups, the risks of incomplete decompression and exiting root injury-related complication were higher in the novice stage.